Peningkatan Minat Baca dengan Program Generasi Masyarakat Gemar Membaca di RPTRA Cililitan Jakarta Timur - Putri Winda Lestari (Universitas Lancang Kuning, 2021)
Reading has many benefits, one of which is opening the world. PISA research shows a low level of Indonesian literacy compared to countries in the world. Needs to be done to foster interest in reading from an early age and apply it to the community. Based on the initial survey, The Cililitan RPTRA has good facilities, such as the availability of a library room. The number of visitors to the library room is small. We can see that there is a low interest in reading at The Cililitan RPTRA visitors. This activity purpose to achieve a high interest in reading in The Cililitan RPTRA, East Jakarta. The method of activity is community development, encapsulated under the name of The Generation of Reading Fondness Program. Based on interviews with The Cililitan RPTRA visitors this program can increase reading interest. Socialization about the importance of reading needs to be done continuously. Other activities that can upgrade interest in reading such as storytelling and educational games. Procurement of books can be a solution to increase reading choices for visitors to The Cililitan RPTRA.